Filmowe reprezentacje seksualności osób niepełnosprawnych – przykład polski - Otto, Wojciech (Przestrzenie Teorii, 2020)
Disability in Polish films is not a marginal issue. As a film topic, it has been explored in many different ways and contexts due to a nexus of diverse relations, trends and social phenomena. All of which have revealed the degree of intensity of the phenomenon as well as its historic changeability. On the one hand, such images have been a reflection of the filmmakers’ interests and, on the other, a source of knowledge on disability and a kind of catalyst for socio-moral transformation shaping the attitudes and behaviour of society towards the disabled. The problem is presented by, images of disabled film characters, which are widely used in Polish cinematography and often built on social stereotypes, as well as by the communicative strategies used by filmmakers in their works on disability. In this context, films about disability have played an opinion-forming role, contributing greatly to an enhanced image of disabled people in society and widening their area of activity. The sexuality of people with disabilities is portrayed as asexuality and hypersexuality, and in Polish cinema it mainly concerns the emotional sphere, and less so the physical.